Community-Engaged Development of Equitable and Scalable Mobile Health Tools for Tobacco TreatmentTake-Home Points - Joanna L. Hart, MD; Tamar Klaiman, PhD, MPH; Michael Scott, BS; George M. Fernandez; Dorothy Sheu, MPH; Aerielle Belk, BS; Jasmine A. Silvestri, MPH; Jannie Kim, MPH; Scott D. Halpern, MD, PhD; Nsenga Farrell, EdD, MA (CHEST Pulmonary)
Background: Tobacco use has a disproportionate impact on older, medically underserved adults. Mobile health (mHealth) tools hold promise for increasing reach of treatment options, yet introduce new barriers to access and use. Research Question: How can investigators incorporate patient and community input into the design and testing of accessible, scalable, and equity-promoting mHealth tobacco treatment tools? Study Design and Methods: We present a model for mHealth tobacco treatment tool development using a longitudinal community-partnered design process. We iteratively developed and refined tools used in a large, pragmatic trial. First, a stakeholder advisory committee (SAC) convened with members including individual patients and representatives from patient and health equity advocacy groups, community and government public health services, clinical program leads, and health system and insurance leaders. Second, we conducted a patient needs assessment to confirm or expand on SAC recommendations using semistructured interviews among patients meeting ≥ 1 medically underserved criteria who smoked tobacco daily. Transcribed interviews were coded and analyzed for patterns of patients’ desired design elements. Results: The SAC recommended key strategies to promote cultural relevance of the tools, maximize engagement of participants, and prevent attrition, which were incorporated into the intervention and trial design. To further refine the approach, we completed interviews with 39 patients from November 2020 to September 2021. Many respondents used telemedicine tools with their clinicians yet were skeptical of their use for tobacco treatment due to lack of facility with mobile technologies. Patients recommended direct support options, avoidance of novel smartphone applications, and customizable features. Interpretation: We provide a model for patient-centered design that incorporates community engagement through longitudinal advisors and wider representation of patients. Longitudinal community engagement that incorporates broad patient perspectives facilitates effective development and deployment of mHealth tools to maximize responsiveness to patient and community needs.